Kesadaran Pajak pada Generasi Muda: Antara Edukasi Perpajakan dan Persepsi terhadap Kewajiban Negara - Desta Dwi Widyadarma; Ni Kadek Gita Sri Wardini; Putu Gede Ardika; Devina Zanati Dwi Aprilianda; Septi Adelina Simanullang (Pajak dan Manajemen Keuangan, 2026)
Tax awareness among the young generation is a crucial issue in national economic development, as taxes are the primary source of state revenue. This study aims to analyze the relationship between tax education and young people's perceptions of state obligations in shaping tax awareness. The method used is a literature review (library research) by analyzing various national scientific journals from the last five years. Results indicate that tax awareness among young people is still relatively low, although digital-based education has shown positive improvements. Perceptions of taxes as a state obligation are strongly influenced by knowledge, trust in government, and tax service quality. Interactive and technology-based education has proven effective in improving understanding and positive attitudes toward taxes. Therefore, synergy between government, educational institutions, and digital media is urgently needed to enhance tax literacy from an early age to ensure future fiscal sustainability.